The principle of non-discrimination in international commercial policy - Hans R. Krämer (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1974)
In an essay with the legal and institutional aspects of discrimination or non-discrimination in international trade, it is impossible to start without a clear definition of what is meant by the term discrimination. Since in common usage almost any behaviour dealing with camparable cases in different ways can be called discrimination, such a term is too vage a basis for legal considerations. At first glance, different meanings of the same term seem to imply a high degree of confusion. This is, however, no speciality of the word discrimination, nor is, in our particular case, the danger of confusion very great. Just because of the fact that in common usage so many forms of behaviour are called discrimination in favour of one party or against another a limited and clear legal definition is such a different thing that a mix-up can easily be avoided. Economists and politicians must only be warned that actions which they describe as discrimination - correct in their own terminology - need not have legal consequences. Only if they have to deal with forms of discrbination which have, at the same time, the characteristics of the legal definition, may they expect or induce legal consequences.
Keywords: 330